1985
DOI: 10.1021/ma00143a005
|View full text |Cite
|
Sign up to set email alerts
|

Properties of polyether-polyurethane block copolymers: effects of hard segment length distribution

Abstract: Two sets of polyether-polyurethane block polymers based on poly(tetramethylene oxide) (PTMO), 4,4'-methylenebis(phenyl isocyanate) (MDI), and butanediol (BD) were prepared in different ways to produce materials with equivalent stoichiometries but different hard segment length distributions. One set of materials was prepared by a one-step polymerization with butanediol as the chain extender. The second series was synthesized by a multistep method using butanediol and/or bis(4-hydroxybutyl) 4,4'-methylenebis(phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
205
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(210 citation statements)
references
References 9 publications
(10 reference statements)
4
205
1
Order By: Relevance
“…This is observed in another study that shows that, in a polycaprolactone (PCL) and MDI PU, PCL crystallinity dominates for low HS/SS values and MDI crystallinity dominates for high HS/SS values [34]. It should be noted that crystallinity is also dependent on the types of HS applied [35,36]. Decrease of phase mixing or increase of phase mixing may, thus, result in crystallinity increase due do domain dominance as may be observed in the results of Heijkants et al [37].…”
Section: Compositionmentioning
confidence: 70%
“…This is observed in another study that shows that, in a polycaprolactone (PCL) and MDI PU, PCL crystallinity dominates for low HS/SS values and MDI crystallinity dominates for high HS/SS values [34]. It should be noted that crystallinity is also dependent on the types of HS applied [35,36]. Decrease of phase mixing or increase of phase mixing may, thus, result in crystallinity increase due do domain dominance as may be observed in the results of Heijkants et al [37].…”
Section: Compositionmentioning
confidence: 70%
“…The results showed that structural units of various forms and sizes develop during polymerization [13][14][15]. Besides a crystalline or at least highly ordered phase, soft and hard segments form corresponding phases which are partially soluble in each other [16][17][18][19][20][21]. Solubility depends very much on the interaction of the components, the urethane groups are capable of forming specific interactions, H-bonds with each other, but also with the soft segments [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the crystallinity of these hard segments in the segmented block copolymers is generally low and a large amount of non-crystallised hard segments is present in the polyether matrix. The crystallisation and the stability of the hard segments are improved when the segments are monodisperse in length [21][22][23][24][25][26][27][28][29][30][31][32][33]. Short monodisperse amide segments crystallise fast and almost completely.…”
Section: Introductionmentioning
confidence: 99%